Transient stability‐oriented assessment and application of preventive control action for power system. Issue 18 (15th July 2019) - Soni, Bhanu P.; Saxena, Akash; Gupta, Vikas; Surana, Simrath L.
Abstract : The modern power system is becoming more complex and dynamic because of increasing penetration of renewable energy resources, operating closer to system capacity for economic benefits. In order to maintain the system stability, the system operator is required to initiate appropriate preventive control action under severe contingencies while satisfying the system operating constraints. Real time transient stability assessment (TSA) of power system is proposed in this paper by using wide area measurement system (WAMS) and phasor measurement units (PMUs). An architecture based on least square support vector machine (LS‐SVM) has been developed to identify the system stability state in real time. Also, this paper proposes a coherency based selection method to identify the appropriate members for generation rescheduling as preventive operation in insecure operating contingency. Rotor angle trajectories based transient stability index (TSI) is employed to classify the generators as either critical or non‐critical generators in a power network. Accordingly preventive control action in the form of generation rescheduling can be initiated to achieve stability. The method has been demonstrated on the IEEE 10‐machines, 39‐bus system. The proposed methodology is effective and capable of handling complex power system models with multiple contingencies.